2019
DOI: 10.15376/biores.14.3.6558-6576
|View full text |Cite
|
Sign up to set email alerts
|

Screening of wild basidiomycetes and evaluation of the biodegradation potential of dyes and lignin by manganese peroxidases

Abstract: Manganese peroxidase (MnP), a crucial enzyme in biodegradation of lignin, is synthesized by most white rot fungi. To obtain novel enzymes with superior biodegradation potential, MnP-producing wild isolates were evaluated for their ability to degrade recalcitrant azo dyes, sulfonephthalein dyes, and kraft lignin. Of 30 wild isolates screened, 18 tested positive for lignin modifying enzymes (LMEs). Thirteen of these isolates were positive for both laccase and MnP, whereas four produced only laccase, and one prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…One of the mechanisms proposed as participating in this process involves both the primary carbon source and the co-substrate acting as co-inducers in the activation of different genes that produce the enzymes that act on the carbon source and the pollutant ( Ahlawat, Jaswal & Mishra, 2022 ; Shimizu et al, 2005 ). In this sense, several reports indicate that the efficiency of dye decolorization can be favored by co-metabolism with different carbon sources, of which glucose, sucrose, fructose, and glycerol are among the most extensively studied ( Civzele, Stipniece-Jekimova & Mezule, 2023 ; Haider et al, 2019 ; Merino, Eibes & Hormaza, 2019 ; Rao et al, 2019 ). The results obtained for the analysis conducted on carbon source consumption and DyP activity levels for both carbon sources analyzed in the present research suggest that the AYG dye may be co-metabolized, thus inducing the production of DyP and other oxidases not evaluated in the experiments conducted by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms proposed as participating in this process involves both the primary carbon source and the co-substrate acting as co-inducers in the activation of different genes that produce the enzymes that act on the carbon source and the pollutant ( Ahlawat, Jaswal & Mishra, 2022 ; Shimizu et al, 2005 ). In this sense, several reports indicate that the efficiency of dye decolorization can be favored by co-metabolism with different carbon sources, of which glucose, sucrose, fructose, and glycerol are among the most extensively studied ( Civzele, Stipniece-Jekimova & Mezule, 2023 ; Haider et al, 2019 ; Merino, Eibes & Hormaza, 2019 ; Rao et al, 2019 ). The results obtained for the analysis conducted on carbon source consumption and DyP activity levels for both carbon sources analyzed in the present research suggest that the AYG dye may be co-metabolized, thus inducing the production of DyP and other oxidases not evaluated in the experiments conducted by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the substrates cellulose: lignin ratios were found to be positively correlated to mycelial growth rates and to mushroom yield of P. ostreatus [ 30 , 31 ], and cotton straw is a substrate with high lignin content. In reports on cotton straw culture of edible mushrooms, it was found that higher yields could be obtained by applying to cotton straw culture of edible mushrooms relative to other crop substrates [ 32 , 33 , 34 , 35 ], in which lignin degrading enzymes played a crucial role [ 36 , 37 , 38 ]. In this study, we first screened the optimum culture conditions for laccase enzyme activity of P. ostreatus Suping 1.…”
Section: Discussionmentioning
confidence: 99%
“…GOD can oxidize glucose to produce D-gluconolactone in the presence of oxygen, and consume oxygen to produce H 2 O 2 . 13 LiP can function normally when H 2 O 2 is present, but excessive H 2 O 2 will induces LiP inactivation. 14 Therefore, the concentration of GOD in the system can increase the activity of LiP within a certain limit, and when the concentration exceeds a certain limit, it will inhibit LiP enzyme activity.…”
Section: Discussionmentioning
confidence: 99%